Methodological landscape in the field of integration site identification of retroviruses and retroviral vectors - Kochergin-Nikitsky, Konstantin; Lavrov, Alexander; Smirnikhina, Svetlana (Frontiers in Bioengineering and Biotechnology, 2025)
Detailed mapping of viral vector integration sites, including retroviral and particularly lentiviral vectors, is critical for assessing their safety in preclinical and clinical studies. Although integration into the host genome follows certain virus-specific patterns, it remains a stochastic event and can cause insertional mutagenesis with diverse consequences, such as oncogene activation. In this review, we trace the evolution of ISA methods applied to retroviruses and derived vectors, from early labor-intensive approaches with limited coverage—such as combined strategies involving restriction analysis, Southern blotting, and subcloning—to modern high-throughput strategies. We discuss key methodologies that shaped the field, including inverse PCR (iPCR), ligation-mediated PCR (LM-PCR), and linear amplification-mediated PCR (LAM-PCR), highlighting their contributions to more comprehensive and unbiased mapping, along with limitations associated with systematic errors stemming from dependence on restriction endonuclease digestion and amplification biases. We also examine recent approaches designed to overcome these limitations, independent of PCR and restriction analysis, which enable a more accurate and undistorted representation of retroviral vector integration profiles. Despite the emergence of new techniques, classical methods—particularly LAM-PCR and its modifications, such as nrLAM-PCR—remain widely used and continue to serve as the standard in many commercial platforms.